Future urban habitation transdisciplinary perspectives, conceptions, and designs - Heckmann, Oliver,|d 1974-; Siew, Man Kok (Hoboken, NJ, USA Wiley Blackwell, 2022)
Around the globe, urban populations are growing at an unpreceded rate, in particular in Asia and Africa. In view of pressing social and environmental challenges it is essential to reimagine current design strategies to build affordable, sustainable, and inclusive communities that can respond to future demographic dynamics, new social practices, and the consequences of climate change. Future Urban Habitation presents an integrative, transdisciplinary approach for developing long-term strategies for urban housing at a different scales. With focus on the rapidly growing cities of Asia, and urban processes in Europe and North-America this volume offers perspectives from both researchers and practitioners involved in multiple aspects of urban habitation. The authors address a range of challenges to urban habitation with four intersecting thematic frameworks: Inclusive Urbanism, High-Dense Typologies for Building Community, Adaptable and Responsive Habitation, and New Tools and Approaches.
Front Matter -- Introduction / Oliver Heckmann -- Inclusive Urbanism. Introduction / Oliver Heckmann -- Towards a New Social Model of the City / Lluís Torrens, Sebastià Riutort, Marta Juan -- Link by Link / Vincent Chua -- Inclusive Smart Community - Towards a Socially Integrated and Enabling Community / Chong Keng Hua, Ha Tshui Mum, To Kien, Yuen Chau -- Designing for Depopulating Conditions - Formulating a Strategic Neighbourhood Framework for Detroit / Ian Dickenson -- Multi-Programmatic Urbanity for Indonesia / Florian Heinzelmann, Daliana Suryawinata -- Affordable Housing and Social Inclusion - The Case of Vienna and Austria / Gerald Kössl -- High-Dense Typologies For Building Communities. Introduction / Oliver Heckmann -- Fostering Community Bonding in High-Density Habitations / Im Sik Cho -- HDB / Jeremiah Lim -- Building Communities in High-Density Singapore - a look at Integrated Design Typology / Siew Man Kok -- Making Sense of 'Community' - A Call for New Kinds of Knowledge to Shape Urban Futures / Saffron Woodcraft -- Adaptive and Responsive Habitation. Introduction / Oliver Heckmann -- Alternative Housing for a Diverse and Inclusive Society / Gérald Ledent -- Type-Figurations - Comfort Zones and Active Grounds / Bernd Vlay -- Promoting Healthy Longevity - The Role of Social Innovation / Yee Wei Lim, Kimberly Teo, Cherylanne Tan, Junyu Ong -- Experiments in Living Together / Colin Neufeld, Sharon Wohl -- Beyond the Unit - Future Hybrid High-Rise Commune / Oliver Heckmann -- New Tools, New Approaches. Introduction / Oliver Heckmann -- Toolkits for Renewable and Regenerative Buildings / Devni Acharya, Emma Boucher, Richard Boyd, Michael Budig, Elisa Magnini, Neil Walmsley -- Social Design - Principles and Practices to Foster Caring Urban Communities / Lekshmy Parameswaran, László Herczeg, Airí Dordas Perpinyà, Adrià Garcia I Mateu -- Computational Design Futures in Housing / Trevor Ryan Patt -- Retooling Architectural Performance Analysis / Timur Dogan, John Alstan Jakubiec.
Includes bibliographical references and index.
Keywords: Housing